2014
DOI: 10.4049/jimmunol.1302064
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decrease in TCR Repertoire Diversity Measured with Deep and Normalized Sequence Profiling

Abstract: The decrease of TCR diversity with aging has never been studied by direct methods. In this study, we combined high-throughput Illumina sequencing with unique cDNA molecular identifier technology to achieve deep and precisely normalized profiling of TCR β repertoires in 39 healthy donors aged 6–90 y. We demonstrate that TCR β diversity per 106 T cells decreases roughly linearly with age, with significant reduction already apparent by age 40. The percentage of naive T cells showed a strong correlation with measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
398
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(454 citation statements)
references
References 59 publications
30
398
2
2
Order By: Relevance
“…However, the diversity of the naïve T cell compartment decreases with age. Deep sequencing of the complementarity-determining region 3 of the T cell receptor (TCR)-β chain from healthy donors revealed that the fraction of expanded clones increases with age (Britanova et al 2014). Similarly, spectratyping of the TCRVB genes revealed the expansion of particular segments (Pennesi et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, the diversity of the naïve T cell compartment decreases with age. Deep sequencing of the complementarity-determining region 3 of the T cell receptor (TCR)-β chain from healthy donors revealed that the fraction of expanded clones increases with age (Britanova et al 2014). Similarly, spectratyping of the TCRVB genes revealed the expansion of particular segments (Pennesi et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…29,34,37 This finding in addition to developmental and signaling alterations alongside with age-related decrease in T-cell generation are all found in cells from older adults, which contribute to functional deficits. The altered signaling is fostered by the persistence of low quantity of pro-inflammatory cytokines and increased production of ROS, both characteristics of InflammAging.…”
Section: Immunology Of Aging In Hiv-infected Patientsmentioning
confidence: 91%
“…In contrast, as CI approaches 1, this indicates a clonal TCR or BCR repertoire, or increased expansion of certain clones in the repertoire. A measure of relative clonotype richness R was also calculated as the average unique clonotypes per cell (assuming one unique clonotype per cell), given by 35 …”
Section: Discussionmentioning
confidence: 99%
“…35 Using ultra-deep sequencing, the authors revealed that diversity of T cell clonotypes decreased almost linearly with age. In addition, there was a significant negative correlation of age with the percentage of na€ ıve T cells in peripheral blood, though this trend was most pronounced up to subjects age 70.…”
Section: E1051922-6 Volume 4 Issue 12 Oncoimmunologymentioning
confidence: 99%
See 1 more Smart Citation